EVAUATION OF WHITE SCHOOL PROJECTS FOR DRUG AND TEMPTATION FREE AT NACHALIANG PITTAYAKOM SCHOOL UNDER THE PHETCHABUN SECONDARY EDUCATION SERVICE AREA - Charoenphon, Phongwiphat (Journal of MCU Nakhondhat, 2024)
This research article aims to: 1) Study the current implementation of the White School Project at Nacheliang Pittayakom School under the Office of Secondary Education Service Area, Phetchabun; 2) Evaluate the outcomes of the White School Project against drugs and vice at Nacheliang Pittayakom School under the Office of Secondary Education Service Area, Phetchabun; and 3) Propose guidelines for elevating the effectiveness of the White School Project against drugs and vice. It is a mixed-methods research study that incorporates both quantitative and qualitative approaches.The research utilized a mixed-method approach. The quantitative study involved a sample group of 25 stakeholders, including administrators, teachers, and students, selected through simple random sampling. The research instrument was a questionnaire, and the statistics used were mean and standard deviation. The qualitative research was conducted in two phases: document analysis and data collection through in-depth interviews and focus group discussions. The tools included an in-depth interview form with 12 key informants and a focus group discussion form with 6 key informants, both selected using purposive sampling. The qualitative data were analyzed using content analysis, triangulated for reliability, and descriptively presented based on the research objectives. The findings revealed that: 1) The school is located in a semi-urban area where the open interactions within the community pose a risk factor, facilitating the spread of drugs among children and youth; 2) The evaluation of the project implementation showed that the input factors were at a high level, the process factors were at the highest level, the output factors were at a high level, and the outcome factors were also at a high level; and 3) The proposed development guidelines include assessing needs in alignment with the school’s context, integrating the project with school activities, creating a learning community where students play active roles and participate in activities, conducting empowering evaluations, and utilizing positive communication strategies.